Sistem Penyeleksi Warna Dan Berat Barang Menggunakan Pergerakan Lengan Robot Empat DOF (Degree Of Freedom) - Abdullah, Abdullah (STIKOM Tunas Bangsa Pematangsiantar, 2017)
The use of robot arm in the system of colour and weight box selection has been done to integrate control system of robot arm moving with colour sensor TCS3200 and weight sensor load cell. The research was conducted by analyzing efficiency and accuracy system of robot arm moving to select colour and weight goods like box. The robot arm moving work suitable instruction of colour and weight sensor reading. At the most important from this system is how to accuracy of colour and weight sensor to detect colour ang weight and accuracy of robot arm moving system can positioning degree moving to take colour with different weight box suitable the place. The result of the analysis proved that robot arm moving had inregrated with colour and weight sensor efficient and effective to do this work as colour and weight box selection accurately.